2011
DOI: 10.17221/95/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of enzymatic system of two different wheat (Triticum aestivum L.) cultivars growing under salt stress

Abstract: Soil salinity and semi-arid and arid climate of Pakistan is a major constraint in agriculture and predominantly in foodstuff production. It limits crop yield and use of land previously uncultivated. Wheat is moderately salt tolerant. A great variation was observed between and within the cultivars (genotypes: S-24 salt tolerant and DN-27 salt sensitive) in relationship to the choice of salinity level (control and treatments: in increment of 25 mol/m<sup>3</sup> NaCl/day to a final level of 80 and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…It was suggested that the higher activities of CAT reduced H 2 O 2 levels in the cell and enhanced the stability of membranes and CO 2 fixation because several enzymes of the Calvin cycle in chloroplasts are very sensitive to H 2 O 2 . However, reports on the effect of environmental stress on CAT activity have been inconsistent [20,31,32]. In this study, both varieties show a significant increase and then followed by a decrease with the increased concentration of perchlorate.…”
Section: Differential Responses Of Twomentioning
confidence: 47%
See 2 more Smart Citations
“…It was suggested that the higher activities of CAT reduced H 2 O 2 levels in the cell and enhanced the stability of membranes and CO 2 fixation because several enzymes of the Calvin cycle in chloroplasts are very sensitive to H 2 O 2 . However, reports on the effect of environmental stress on CAT activity have been inconsistent [20,31,32]. In this study, both varieties show a significant increase and then followed by a decrease with the increased concentration of perchlorate.…”
Section: Differential Responses Of Twomentioning
confidence: 47%
“…Basu et al also demonstrated the activities of SOD were decreased in IR-29 (salt-sensitive) and PB (aromatic Pusa Basmati), whereas they were unaltered in Pokkali (salt-tolerant) when they were subjected to drought stress for two days [20]. But some studies show SOD activity will be enhanced when plants are subjected to environmental stresses [32,33]. However, the response of SOD activity to environmental stresses is reported to be dependent on stress intensity, species, and age of the plants exposed to stress [31,34,35].…”
Section: Differential Responses Of Twomentioning
confidence: 99%
See 1 more Smart Citation
“…This increase may be due to the synthesis of reactive oxygen species (ROS) (Baxter et al, 2014 andDietz et al, 2016). Antioxidant enzymes such as peroxidase and catalase are scavenging enzymes which regulate hydrogen peroxide (H 2 O 2 ) content, thus inhibiting the production of OH − radicals which produced from photorespiration and β-oxidation of fatty acids in organelles during metabolic processes (Rout &Shaw, 2001 andBhutta, 2011). Damaging of membranes fatty acids could produce small hydrocarbon fragments including MDA which is an important sign of membrane system injury (Masood et al, 2006 andMoussa, 2008).…”
Section: Antioxidant Defense Systemmentioning
confidence: 99%
“…The same situation is observed in the Zlatna genotype when it comes to SOD activity on both soil types and in all tested stages. By examining the effect of NaCl on the growth of wheat cultivars, Bhutta (2011) concluded that the scavenging of superoxide radicals by SOD had not been done perfectly. However, there are numerous studies that prove that this enzyme directly affects the reduction of oxidative damage during salt stress (Jalali-e-Emam et al, 2011;Muchate et al, 2016).…”
Section: Discussionmentioning
confidence: 99%